EFEKTIVITAS KEBIJAKAN PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) SKALA MIKRO DALAM PENYEBARAN COVID-19 DI DESA WAREMBUNGAN - MAWUNTU, PRICILIA; RARES, JOYCE; PLANGITEN, NOVVA (Sam Ratulangi University, 2022)
The purpose of this study was to determine the effectiveness of the Micro-Scale Community Activity RestrictionPolicy (PPKM) in the spread of COVID19 in Warembungan Village. This study uses a qualitative approachwith a descriptive research model. Meanwhile, the data collection technique used in this research is throughinterview techniques with informants, observation techniques to research locations and documentationtechniques for existing research results. The theory used is the theory of Riant Nugroho (2018) regarding fiveprinciples that must be met in policy effectiveness, namely the right policy, the implementation target, the righttarget, the right environment and the right process. Based on the results of the study, it was shown that theeffectiveness of the micro-scale PPKM policy in the spread of COVID19 in Warembungan Village was carriedout well. The results related to this policy are that there is no increase in the number of COVID19 inWarembungan village, and with this policy the chaos at night has reduced. However, the implementation ofthis policy cannot be separated from the various obstacles that exist such as the presence of some people whostill do not care and are indifferent to the policies that are being implemented, the lack of socializationprovided and not far in advance, people outside Warembungan village who complain about this policy. . Thesuggestion from the researcher is that in the future the implementation of this policy needs to be socializedwell in advance and reviewed whether the target to be intervened is appropriate or not.Keywords: Effectiveness, PPKM, Covid 19